Frequency of Positive Anti-CCP Antibodies in Patients of Rheumatoid Arthritis with Negative Rheumatoid Factor: A Cross-sectional Retrospective Data-based Study - Nauman Ismat Butt; Muhammad Sohail Ajmal Ghoauri (Indian Journal of Medical Biochemistry)
Objective: To investigate the frequency of positive anti-cyclic citrullinated peptide (CCP) antibodies in rheumatoid arthritis (RA) patients with negative rheumatoid factor (RF) from Lahore, Pakistan. Materials and methods: This retrospective cross-sectional observational study was conducted at the Department of Medicine and Allied, Azra Naheed Medical College, Superior University Lahore. The 2010 ACR Diagnostic Criteria were used to define RA. The medical records of all patients with RF-negative RA from January 2022 to December 2023 were included in the study. Patients with incomplete data and seronegative arthritis due to other causes were excluded from the study. Retrospective data of 78 RF-negative RA patients, including basic, demographic, and clinical information such as age, sex, anti-CCP antibody status, and disease severity, were assessed and recorded. Statistical Package for the Social Sciences (SPSS) version 26 was used for data entry and analysis. Results: The mean age was 43.8 ± 15.8 years with 10 (12.8%) males and 68 (87.2%) females. Mean duration of disease was 9.1 ± 7.8 years with 62 (79.5%) patients have disease duration more than 3 years. Mean DAS-28 score was 4.5 ± 1.7 with 48 (61.5%) patients having active disease (DAS-28 score >3.2). Anti-CCP antibodies were observed in 32 patients (41.0%). Stratification of data with regard to anti-CCP antibodies revealed a significant association with sex but not with age, duration of disease, or disease severity. Conclusion: More than one-third of RA patients with negative RF test results had positive anti-CCP antibodies.